Comparative Microstructural Study on Mechanical Properties of Concrete Enhanced with Graphite and Graphene Compound - Sudheer, P.; S. Chandramouli, Dr (International Journal of Engineering and Technology, 2018)
The present study is based on nano technology and came up with the idea of introducing nanoparticles in the raw materials used for construction. Nano materials are available in three principal shapes 0, 1 and 2 Dimensional nanoparticles. 0D and 1D nanofibers are such as carbon nanotubes and nanosilica compounds. This study has investigated the physical and chemical properties of graphite and graphene compound and its applicability in construction industry. Graphene has created interest as it is believed to improve the strength of concrete allowing the possibility of controlling properties of concrete. In this work graphene is used as a reinforcing additive in cement-based mortar and concrete. Own Graphene compound is prepared using conventional graphite and concentrated hydrogen peroxide in the laboratory due to the unavailability of graphene. As a part of microstructural investigation, SEM and EDS analysis on graphite and graphene compounds before and after implementation are carried out in the laboratory. Then the two compounds are replaced as a part of small percentage in cement mortar cubes casted for various proportions. The mechanical properties of cement-based composites are studied after incorporating of graphite and graphene compounds at low dosages in concrete and then the results are compared.